KAJIAN TENTANG MEMORI - Dicky Hastjarjo (Faculty of Psychology Universitas Gadjah Mada, 2008)
Memory has been a multidisciplinary science where psychology is one of its core component. Therefore, the word “memory” itself referred to a plural concept. Tulving (2007) explained three reasons why it was important to discuss about memory concept. The question of “what” is memory is as important as the question of “how and why”.